T.R.Y. - tarot reading yourself - Martha Dís Brandt (2006)
This document is the dissertation for my final year project 2005-2006 in Computer Science of the Information Technology Faculty of the University of Akureyri. My project is called “T.R.Y. – Tarot Reading Yourself” where I created a tarot reading system using the programming language CLIPS. The system was created for individuals who wish to seek spiritual guidance from the tarot cards directly, i.e. so they would not require another person to do it for them. This dissertation defines the problem to be solved, discusses my approach to the problem, provides detailed information about how I designed and implemented the system, explains how the final system works, tells of further work that can be done on the system and my conclusion regarding the project as a whole.